New Frontiers in Information and Production Systems Modelling and Analysis Incentive Mechanisms, Competence Management, Knowledge-based Production - Różewski, Przemysław; Novikov, Dmitry; Bakhtadze, Natalia; Zaikin, Oleg.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book demonstrates how to apply modern approaches to complex system control in practical applications involving knowledge-based systems. The dimensions of knowledge-based systems are extended by incorporating new perspectives from control theory, multimodal systems and simulation methods.  The book is divided into three parts: theory, production system and information system applications. One of its main focuses is on an agent-based approach to complex system analysis. Moreover, specialised forms of knowledge-based systems (like e-learning, social network, and production systems) are introduced with a new formal approach to knowledge system modelling.   The book, which offers a valuable resource for researchers engaged in complex system analysis, is the result of a unique cooperation between scientists from applied computer science (mainly from Poland) and leading system control theory researchers from the Russian Academy of Sciences' Trapeznikov Institute of Control Sciences.
Teams.- Incentive Mechanisms for Multi-Agent Organizational Systems -- Optimal organizational structures for change management in production -- Knowledge-based models of nonlinear systems based on inductive learning -- Multiple criteria decision support system for tender consortium building within the cluster organization -- Guideline for MCDA method selection in production management area -- Declarative modelling driven approach to production orders portfolio prototyping -- A knowledge-based system for new product portfolio selection.
Keywords: Computational intelligence; Artificial intelligence; Industrial engineering; Production engineering; Control engineering; Robotics; Automation; Game theory; Computational Intelligence; Artificial Intelligence; Industrial and Production Engineering; Control, Robotics, Automation; Game Theory